SPEKTRUM PADA GRAF REGULER KUAT - Rizki Mulyani; Triyani Triyani; Niken Larasati (Universitas Jenderal Soedirman, 2013)
This article studied spectrum of strongly regular graph. This spectrum can be determined by the number of walk with lenght l on connected simple graph, equation of square adjacency matrix and eigen value of strongly regular graph.